Change of authorship of Aphodius and Oryctes to Hellwig, 1798 (Insecta: Coleoptera: Scarabaeidae) - Alonso-Zarazaga, Miguel Angel; Krell, Frank-Thorsten (Zootaxa, 2011)
The dung beetle genus Aphodius and the rhinoceros beetle genus Oryctes rank among the more widely used scientific insect names. Both have been attributed to Johann Karl Wilhelm Illiger who had introduced those names in his "Verzeichniss der Käfer Preussens" in 1798. The names are undisputed and stable. The discovery of a preview of Illiger’s book, published eight months earlier, prompts a change of authorship to Hellwig (1798) for both of these generic names.